P010 Designing a fast-track pathway for the diagnosis of giant cell arteritis in a busy Ambulatory Emergency Care Unit based on British Society of Rheumatology guidelines. (23rd April 2022) - Lakhani, Priyanka M; Ali, Sabreen; Sames, Edward; Agarwal, Paras; Lisk, Radcliffe
Abstract: Background/Aims: BSR states: "GCA is a medical emergency. Patients should be evaluated by a specialist ideally on the same working day if possible and in all cases within 3 working days." Currently in this DGH there is no pathway for diagnosis and management of GCA. Patients are referred from their GP and A&E directly to the Ambulatory emergency care unit (AECU), but it is not guaranteed they will be seen by a specialist within 3 days. We were also receiving inappropriate referrals for possible GCA such as patients under the age of 50 or chronic headache. We have 7-day access to acute ultrasonography in this DGH. We aimed to utilise this service in our fast-track GCA pathway. Aims: 1. All patients with suspected GCA to be seen within 3 working days by specialist. 2. Reduce the number of inappropriate referrals. 3. Reduce irreversible sequelae (visual loss, scalp tissue necrosis and stroke) Methods: We developed a fast-track pathway containing referral criteria, directions for obtaining urgent ultrasonography and management advice. This was uploaded onto the intranet and was put up as posters in the AECU (see pathway). Baseline measurement: data were collected from ambulatory care referrals over a 5-month period. 29 patients were referred as possible GCA. After introduction of the pathway, data were re-collected over a 3-month period, with nine patients referred as possible GCA. Results: Outcomes measured: The percentage of inappropriate referrals decreased by 16% . The percentage of patients reviewed by rheumatology within 3 days increased from 44% to 78%. The percentage of sequelae did not change. Visual loss occurred in both groups at presentation (transient in one patient). Prior to pathway implementation, 31% of patients referred had raised CRP/ESR. ESR/CRP was not tested in 34% of referrals. Following implementation, 100% of patients had CRP and ESR tested; of these 66% had raised CRP/ESR. Conclusion: We have shown that having a fast-track pathway in place results in higher likelihood of a specialist evaluation within 3 days, as per BSR guidelines. To improve we suggest implementation of dedicated same-day AECU appointments for Rheumatology Specialists. Disclosure: P.M. Lakhani: None. S. Ali: None. E. Sames: None. P. Agarwal: None. R. Lisk: None.